2006
DOI: 10.1021/cm060644r
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide-Containing Metallomesogens with Low Transition Temperatures

Abstract: Lanthanide-containing liquid crystals exhibiting a mesophase close to room temperature were obtained by adduct formation between a long-chain salicylaldimine Schiff base and tris(2-thenoyltrifluoroacetonato)-lanthanide(III) complexes or tris(benzoyltrifluoroacetonato)lanthanide(III) complexes. The mesophase was identified as a smectic A phase. The temperature range of the mesophase was found to decrease over the lanthanide series, and no mesophase was observed for the complexes of the smallest lanthanide ions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 92 publications
2
35
0
Order By: Relevance
“…[37] In most of the earlier examples, the mesomorphism was not induced by the β-diketonate ligand, but rather by a mesogenic Schiff base ligand. [14,22,66] No liquidcrystal phases are observed for the complexes of the light lanthanides (Ln = La, Nd), whereas the complexes of the heavy lanthanides exhibit a monotropic smectic A phase. In the smectic A phase, the complexes are arranged in layers with interdigitation of the molten aliphatic chains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] In most of the earlier examples, the mesomorphism was not induced by the β-diketonate ligand, but rather by a mesogenic Schiff base ligand. [14,22,66] No liquidcrystal phases are observed for the complexes of the light lanthanides (Ln = La, Nd), whereas the complexes of the heavy lanthanides exhibit a monotropic smectic A phase. In the smectic A phase, the complexes are arranged in layers with interdigitation of the molten aliphatic chains.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, there has been considerable activity in the research field of lanthanide-containing liquid crystals (which are also called lanthanidomesogens). [2,[9][10][11] Different types of ligands were used to design new classes of lanthanidomesogens: Schiff bases, [12][13][14][15][16][17][18][19][20][21][22] β-enamino ketones, [23] alkanoates, [24,25] 4-alkoxybenzoates, [26][27][28] phthalocyanines, [29,[29][30][31][32][33] porphyrins, [34,35] imidazo [4,5-f] [1,10]phenanthrolines, [36] β-diketonates, [37] crown ethers, [38][39][40] 2,6-bis-(benzimidazol-2Ј-yl)pyridines, [11,41,42] and polyoxometalatesurfactant complexes. [43] Most examples of lanthanidomesogens are thermotropic liquid crystals, although some examples of lyotropic lanthanidomesogens have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Time-resolved detection of europium(III) forms the basis of several biomedical analyses and bioanalytical assays [33,93,[783][784][785][786]. In section 3.8, it is described how time- complexes [790]. These studies showed that the monitoring of the luminescence lifetimes is superior compared to monitoring of the luminescence intensity as a function of the temperature.…”
Section: Decay Processes and Lifetimesmentioning
confidence: 99%
“…These characteristics enable them to have wide application in responsive luminescent stains for biomedical analysis with temporal and spectral discrimination, [1][2][3][4][5][6][7][8][9] and to find use in development for liquid-crystal displays, [10][11][12][13] laser materials [14][15] and optoelectronic emitters. [16][17] Generally, the excellent luminescence properties of lanthanide complexes are attributed to the intramolecular energy transfer between the organic ligands and chelated metal ("antenna effect").…”
Section: Introductionmentioning
confidence: 99%